2014
DOI: 10.1371/journal.pone.0097487
|View full text |Cite|
|
Sign up to set email alerts
|

De Novo Assembly of Expressed Transcripts and Global Transcriptomic Analysis from Seedlings of the Paper Mulberry (Broussonetia kazinoki x Broussonetia papyifera)

Abstract: The paper mulberry is one of the multifunctional tree species in agroforestry systems and is also commonly utilized in traditional medicine in China and other Asian countries. However, little is known about its molecular genetics, which hinders research on and exploitation of this valuable resource. To discern the correlation between gene expression and the essential properties of the paper mulberry, we performed a transcriptomics analysis, assembling a total of 37,725 unigenes from 54,638,676 reads generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The complete chloroplast genome of an economic and ecological plant, paper mulberry (Broussonetia kazinoki 3 Broussonetia papyifera) The paper mulberry, hybridized by Broussonetia kazinoki  Broussonetia papyifera, is a species of Moraceae, which is distributed in Eastern Asia and pacific countries (Xianjun et al 2014). The species has important economic values and ecological values.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…The complete chloroplast genome of an economic and ecological plant, paper mulberry (Broussonetia kazinoki 3 Broussonetia papyifera) The paper mulberry, hybridized by Broussonetia kazinoki  Broussonetia papyifera, is a species of Moraceae, which is distributed in Eastern Asia and pacific countries (Xianjun et al 2014). The species has important economic values and ecological values.…”
Section: Mitogenome Announcementmentioning
confidence: 99%
“…In our study, a total of 1,337 TFs identified from the transcriptome data of the paper mulberry could be classified into 55 families and 578 TFs of them had complete ORF. These TFs comprised of more than 3.5% of the genes of this plant [ 22 ]. Although the genome of paper mulberry has not been sequenced and its genes number might be underestimated, this ratio was much closed to that of other genome known plants, such as C. sativa , Fragaria vesca and Vitis vinifera (Figure 6 ) and it is less than that of Arabidopsis and rice.…”
Section: Discussionmentioning
confidence: 99%
“…Raw sequence data were generated by Illumina pipeline and have been available in NCBI’s Short Read Archive (SRA) database ( http://www.ncbi.nlm.nih.gov/Traces/sra/sra.cgi ) under accession number SRP029966. All of the Illumina reads generated from different cDNA libraries were de novo assembled with Trinity program to form the global transcriptome of the paper mulberry [ 22 ]. For the functional annotation, unigenes were firstly aligned by Blastx to protein databases nr (E ≤ 1e-5), retrieving proteins with the highest sequence similarity to the given unigenes along with their functional annotations.…”
Section: Methodsmentioning
confidence: 99%
“…Paper mulberry, Broussonetia papyifera, B. kazinoki × B. papyifera are all used to called the tree, while it may not the same tree [36]. In recent year, a hybrid variety for paper mulberry was bred [15,37]. The breeding process is showed in Fig.…”
Section: Introductionmentioning
confidence: 99%